PERBEDAAN JENIS IKLAN SEKOLAH TERHADAP SIKAP KONSUMEN DALAM MEMILIH SEKOLAH - Yulfi Zahara; Gumgum Gumelar (Journal of Research and Measurement in Psychology, 2014)
ABSTRACT The aim of this study is to determine comparison school ads toward consumer attitudes in choosing the school. The research was conducted in Bekasi and Halimun during November-December 2013. This study used comparative method. Incidental sampling was used as sampling technique. A total of 180 respondens participated in this study. Attitudes toward school ads instruments by Lisa Lamhapsari’s research is used to this research. Statistical descriptive that used in this study were performed with SPSS 17.0 for windows. The result of this study showed that there are differences consumer attitudes toward school ads based on source messages . School ads with celebrity fact is the most positive consumer attitudes. School ads with opinion by ordinary people is the negative in consumer attitude. Conclusion of this research that the most effective school ads for consumer is the fact testimonial ads by celebrity. Keyword: Consumer Attitudes, School Ads